Parents’ participation in School Management Shuras (SMS) in Afghanistan: Barriers and opportunities for parental involvement in the public schools Of Ishkshim - Shaida, Ali Nazar (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Science in Early Child Development, 2021.